2023
DOI: 10.1098/rstb.2022.0411
|View full text |Cite
|
Sign up to set email alerts
|

Order and change in art: towards an active inference account of aesthetic experience

Sander Van de Cruys,
Jacopo Frascaroli,
Karl Friston

Abstract: How to account for the power that art holds over us? Why do artworks touch us deeply, consoling, transforming or invigorating us in the process? In this paper, we argue that an answer to this question might emerge from a fecund framework in cognitive science known as predictive processing (a.k.a. active inference). We unpack how this approach connects sense-making and aesthetic experiences through the idea of an ‘epistemic arc’, consisting of three parts (curiosity, epistemic action and aha experiences), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 123 publications
1
17
0
Order By: Relevance
“…Interestingly, our account is aligned with what has already been argued by some advocates of the PPF perspective, who point out that people do not solely pursue immediate certainty [70]. As further elaborated by Van de Cruys et al [1], this perspective acknowledges that people sometimes balance their desire for order and closure with a preference for surprise. This occurs because tolerating or even seeking uncertainty offers several long-term advantages.…”
Section: (A) Non-directional Goals To Seek Versus Avoid Certaintysupporting
confidence: 86%
“…Interestingly, our account is aligned with what has already been argued by some advocates of the PPF perspective, who point out that people do not solely pursue immediate certainty [70]. As further elaborated by Van de Cruys et al [1], this perspective acknowledges that people sometimes balance their desire for order and closure with a preference for surprise. This occurs because tolerating or even seeking uncertainty offers several long-term advantages.…”
Section: (A) Non-directional Goals To Seek Versus Avoid Certaintysupporting
confidence: 86%
“…For example, the finding that the Default Network [60,61] plays an important role in aesthetic experiences refers to a state in which change is prepared by the suppression of certain action tendencies that might be formed by the context of experience, and thus explain the special status of art in human culture. In this respect, the special brain state at least implied by such findings might be seen as the neurophysiological condition to what Van de Cruys et al [7] propose as 'the friction of prediction error creates the potential to (unexpectedly) make progress in structuring the stimulus, and, when this structuring happens by means of one's own epistemic (cognitive-behavioural) faculties, it sparks positive affect and situates the discovered structure in the outside world' ( p. 14).…”
Section: A (Brief ) Historical Search For Elements Of Predictive Proc...mentioning
confidence: 80%
“…Moreover, regarding the emotional processing of ambiguity, a state not much appreciated in everyday life, Jakesch et al [47] found that zygomaticus major muscle activation was higher and corrugator supercilii activation was lower for ambiguous versus non-ambiguous versions and suggested that this might 'reflect a positive continuous affective evaluation to visual ambiguity in paintings' and further suggested this as 'indirect evidence for the hypothesis that visual stimuli classified as art, evoke a safe state for indulging into experiencing ambiguity, challenging the notion that processing fluency is generally related to positive affect' ( p. 1; see also [48,49] for similar findings relating ambiguity or challenging art to the brain). As one example from the emerging PP discourse, in their paper, Van de Cruys et al [7] present a simple ambiguous Hebb figure to illustrate a cycle of processing stages as 'processing errors' that meander between ambiguity (i.e. prediction errors) and resolutions at different levels.…”
Section: A (Brief ) Historical Search For Elements Of Predictive Proc...mentioning
confidence: 99%
“…R. Soc. B 379: 20220416 see [31,62]). This sense-making drive is rooted in the intrinsic motivation to learn and explore [63] and might be compatible with a proactive conception of perception (that is central to PP, [2]).…”
Section: (B) Affective Dynamicsmentioning
confidence: 99%